ERROR ANALYSIS ON THE USE OF SIMPLE PAST TENSE IN RECOUNT TEXTS WRITTEN BY THE 8th GRADE STUDENTS OF SMPN 3 PROBOLINGGO - ISWAHYUNI, SANTI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Iswahyuni, Santi. 2014. Error Analysis  on  The  Use of  Simple  Past  Tense  in Recount    Texts    Written    by    The    8th  Grade  Students  of  SMPN  3 Probolinggo.  Study  Program  of  English,  Department  of  Languages  and Literature,  Faculty  of  Cultural  Studies,  Universitas  Brawijaya.  Supervisor: Fatimah; Co-supervisor: Ida Puji Lestari.Keywords : error analysis, surface strategy taxonomy, source of error, recount textThis  research  is  about  errors  occured  in  the  students’  writing  in  using simple  past  tense  in  recount  text  by  the  eighth  grade  students  of  SMPN  3 Probolinggo.  Learning  a  second  language  is  difficult  for  students  because  they have  to  learn  about  the  grammar  of  the  second  language.  In  learning  a  second language, making errors cannot be avoided because the students borrow the rules of their first language to a second language. Most students assume that writing is the  most  difficult  skill.  Thus,  students  often  make  errors.  This  study  was conducted based on the consideration that simple past tense has an important role in writing recount text. There are two problems in this study; what types of errors found  and  the  sources  of  errors  found  in  the  recount  text. The  purposes  of  this study are  to  identify and classify  the  types of errors  found and  to  investigate  the sources of the errors found.  The  research  method  used  is  qualitative  approach.  This  research  was conducted at SMPN 3 Probolinggo. The population  in  this study were  the eighth graders  of  SMPN  3  Probolinggo.  The  classes  used  as  the  sample  were  seven classes  taught  by  the  same  teacher.  The  total  population  was  191  students  of which  19  students were  selected  as  the  sample  based  on  the  best English  score from each class. The steps of data analysis consist of identifying errors, describing the error, explaining the error, and drawing conclusions. To analyze the data, this study used  types of error based on Dulay’s  theory  and  source of  error based on Lott’s theory. The  results  showed  that  based  on  surface  strategy  taxonomy,  there were omissions  (24%),  additions  (7%),  misformations  (65%)  and  misordering  (4%). Misformation was  the highest  type of error occurred. The sources of those errors were overextention of analogy error (1%),  transfer of structure errors (94%), and interlingual/intralingual errors (5%). Eventhough the students have good score in their English, they still make a lot of errors and tend to apply the rules of their first language when they do not know the rules of the second language.   This  study  is  useful  for  students  and  teachers.  It  is  expected  that  the English teachers give more pratices to improve the English ability of the students. It  is  required  for  eighth  grade  students  to  improve  their  English  grammar especially in writing.